Parameter extraction method for Cauer model considering dynamic thermal diffusion boundaries in IGBT module. (January 2023) - Dong, Chao; Hu, Jingwei; Du, Mingxing
Abstract: Considering the change of working conditions, the calculation of thermal resistance and thermal capacity with the fixed shape of heat conduction area will result in a large calculation error for junction temperature of the Cauer model. Based on the conventional Cauer model, a circular heat conduction area is chosen to calculate the thermal resistance and thermal capacity in this manuscript, which avoids the inaccurate calculation of heat conduction area under different working conditions by the fixed heat diffusion angle method. In addition, a few fiber grating sensors are arranged on the baseplate to track the selected isotherm in real time, and update the isotherm as the thermal diffusion boundary according to the simulation rule. Furthermore, accurate thermal resistance and thermal capacity values are calculated online according to the circular heat conduction area that its boundary is the selected isotherm. Finally, the correction of the Cauer model with real-time updated thermal resistance and thermal capacity can calculate a more accurate junction temperature.